The PISCES Approach to Cyber Education (Journal of The Colloquium for Information Systems Security Education, 2024)
The following is a partner paper published to the CISSE journal. For more information, please visit the PISCES website.The Public Infrastructure Security Cyber Education System (PISCES) program has had significant impact on the cyber security posture of small municipalities and has helped develop qualified entry-level cyber analysts with real-world experience. Due to the ever-evolving nature of cyber security, adjusting our cyber security educational approach to be just as flexible is of dire importance. This paper will address how the PISCES program educates the students and partners with the municipalities, the aspects of cyber security training that PISCES does not cover and makes suggestions on how cyber security training can be applied to other situations.
Keywords: cyber security training; talent gap; pedagogy